Seven‐inch large‐size synthesis of monolayer hexagonal BN film by low‐pressure CVD. Issue 5 (12th December 2015) - Wu, Chenping; Soomro, Abdul Majid; Sun, Feipeng; Wang, Huachun; Liu, Chuan; Yang, Xiaodong; Kang, Junyong; Cai, Duanjun
Abstract : We report the large‐size synthesis of atomic monolayer hexagonal boron nitride (h‐BN) film on flexible Cu foil by a low‐pressure chemical vapor deposition (CVD) method. The borazane powder was used as the precursor carried by mixed hydrogen/argon gases. By rolling the Cu foil substrate into a cylindrical shape, wafer‐scale monolayer h‐BN film has been achieved at a size over 7 in. With the aid of PMMA, the h‐BN monolayer was transferred onto a 4″ Si wafer for characterization and further electrical applications. This technique could be transferred to thin‐film growth on any flexible substrates.